MIKROALGAE SEBAGAI SUMBER ENERGI TERBARUKAN YANG RAMAH LINGKUNGAN - Amin, Sarmidi (Jurnal Teknologi Lingkungan, 2009)
Microalgae as biomass are a potential source of renewable energy and they can beconverted into energy such as biofuel oil and gas. This paper presents a briefreview on the main conversion process of microalgae becoming energy. Sincemicroalgae have high water content, then not all biomass energy conversion processescan be applied. By using thermochemical process it can be produced oil and gas,and by using biochemical process it can be produced ethanol and biodiesel. Theproperties of microalgae product is almost similar to offish and vegetables oil andtherefore it can be considered as a substitute of fossil oil.